Boosting Electrocatalytic Activity of Binary Ag-Fe-doped Co2P Nanospheres as Bifunctional Electrocatalysts for Overall Water Splitting. (20th September 2017) - Yan, Kai-Li; Shang, Xiao; Zhang, Li-Ming; Dong, Bin; Liu, Zi-Zhang; Chi, Jing-Qi; Gao, Wen-Kun; Chai, Yong-Ming; Liu, Chen-Guang
Graphical abstract: Highlights: Ag-Fe-Co2 P nanosphere is prepared as bifunctional electrocatalyst for HER and OER. The binary Ag-Fe-doping may improve of electronic structure of active site of Co2 P. Ag-Fe-Co2 P has the obvious enhancement of activity for HER and OER in 1 M KOH. Ag-Fe doping may provide the improved conductivity and electron-donating ability. Abstract: The binary Ag-Fe-doped Co2 P (Ag-Fe-Co2 P) nanospheres have been prepared as bifunctional electrocatalysts for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using Ag-Fe-Co hydroxides nanospheres as precursors. XRD and XPS confirm the formation of Ag-Fe-Co2 P. SEM and TEM demonstrate that Ag-Fe-Co2 P has uniform nanospherical morphology composed of vertical nanosheets, which imply the more exposed active sites for water splitting. For HER measurements in 1 M KOH, Ag-Fe-Co2 P with the overpotential of only 41 mV to drive current density of 10 mA cm −2 . Remarkably, to achieve current density of 100 mA cm −2 for OER, Ag-Fe-Co2 P requires overpotential of 220 mV, which is obviously less than that of Fe-Co2 P. Furtherly, when Ag-Fe-Co2 P was used as the electrocatalyst for both cathode and anodic, a cell voltage of 1.53 V was able to reach 100 mA cm −2 in 1.0 M KOH, outperforming most reported nonprecious electrocatalysts. The obvious enhancement in activity of Ag-Fe-Co2 P for HER and OER derived from its high conductivity, electron-donating ability and augmented accessibility of active sites. Therefore, designing multiple metal doped transition metal phosphides with unique nanostructure may be a promising way for efficient overall water splitting.